STRATEGI MANAJEMEN RISIKO PADA OPERASIONAL BANK BTN SYARIAH DI MASA PANDEMI COVID - 19 - Suci Nurani; Isfandayani Isfandayani; Purnama Putra (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
This study aims to 1) analyze the general operational description of Bank BTN Syariah kc Bekasi during the bank's operation during the pandemic. 2) identify the type of risk faced. 3) analyze the risk mitigation by Bank BTN Syariah KC Bekasi. 4) Recommend alternative strategies that can be implemented for Bank BTN Syariah as long as the bank operates during the Covid-19 pandemic. This research combined research with primary and secondary data. Data collection techniques used literature studies, documentation, interviews, and questionnaires. The data analysis method uses the IFE, EFE, and Grand Strategy methods. The results of this study show that while operating during a pandemic, banks face operational, reputation, and financing risks. The results of the internal analysis of the value of IFE are 3.44, and the external analysis of EFE is 3.22. The company's position in the matrix The Grand Strategy is in quadrant one, so the strategic recommendations are market development strategy, product development, and market penetration